Gata6 Haploinsufficiency Leads to Aortic Valve, Conduction System and Limbs Defects - Gharibeh, Lara (Université d'Ottawa / University of Ottawa, 2018)
Cardiovascular diseases are the leading cause of morbidity and mortality worldwide. Congenital heart disease (CHD) is a risk factor for premature cardiovascular complications. Great advances have occurred in the past years leading to the identification of several genes essential for proper cardiac formation such as GATA4/5/6 mutated in some individuals with CHD. GATA6 is a zinc finger transcription factor whose presence is crucial for early embryonic development. GATA6 is expressed in many cell types of the heart including myocardial, endocardial, neural crest, and vascular smooth muscle. In human, mutations in GATA6 result in variable cardiac phenotypes. The objective of this thesis was to determine the roles that GATA6 play in the different cell types of the heart and to elucidate the molecular basis of the cardiac defects associated with Gata6 haploinsufficiency. For this, a combination of cell and molecular techniques were used in vitro and in vivo. First, we show that Gata6 heterozygozity leads to RL-type bicuspid aortic valve (BAV)- the most common CHD affecting 2% of the population. GATA6-dependent BAV is the result of disruption of valve remodeling and extracellular matrix composition in Gata6 haploinsufficient mice. Cell-specific inactivation of one Gata6 allele from Isl-1 positive cells, but not from endothelial or neural crest cells, recapitulates the phenotype of Gata6 heterozygous mice revealing an essential role for GATA6 in secondary heart field myocytes during valvulogenesis. We further uncovered a role for GATA6 as an important regulator of the cardiac conduction system and revealed that GATA6 expression regulates the activity of the cardiac pacemaker. GATA6 exerts its role via regulation of the cross-talk among the different cell types of the SAN. Lastly, some CHDs are characterized by abnormalities of both the limbs and the heart such as the Holt Oram syndrome (caused by mutation in TBX5 transcription factor). The molecular basis for limb-heart defects remain poorly understood. In the course of this work, we discovered that Gata6 haploinsufficiency resulted in a partially penetrant polysyndactyly (extra digits fused together) phenotype. Together, the data provide novel molecular and cellular insight into GATA6 role in normal and pathologic heat development. Our results also suggest that GATA6 should be added to the list of genes whose mutations are potentially associated with heart and limb abnormalities. Better knowledge of the molecular basis of CHD is a prerequisite for the development of diagnostic and therapeutic strategies to improve care of individuals with congenital heart disease.
Keywords: GATA factors; Congenital heart diseases; Atrial fibrillation; Bicuspid aortic valve disease